UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI KENAKALAN PESERTA DIDIK DI SEKOLAH DASAR NEGERI BULUREJO 2 DIWEK JOMBANG - Eny Fatimatuszuhro Pahlawati; Shofwatal Qolbiyyah; Siti Aminatuzzuhroh (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2023)
The aim of this research is to find out how Islamic Religious Education teachers try to overcome student delinquency at the Bulurejo 2 Diwek Jombang State Elementary School. This type of research is qualitative research, using a descriptive approach. The data collection technique is through observation, interviews and documentation. Meanwhile, the data analysis technique uses qualitative descriptive analysis which is carried out in depth through 3 stages, namely: data reduction, data presentation, and drawing conclusions or verification. The results of the research show that the efforts of Islamic religious education teachers to overcome student delinquency at the Bulurejo 2 Diwek Jombang State Elementary School were carried out by collaborating with students' parents, providing advice, guidance, motivating students, approaching and reprimanding students who commit a violation. Obstacles experienced by Islamic religious education teachers in dealing with student delinquency at Bulurejo 2 Diwek Jombang State Elementary School include: lack of cooperation between teachers and parents of students, limited time in providing guidance to students, students not being open with teachers, and free association of students outside school hours.